2017
DOI: 10.22159/ijcpr.2017v9i6.23430
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study of Drug Utilisation Pattern and Pharmacovigilance of Antipsychotics

Abstract: Objective: Drug Utilization Research (DUR) was defined by the WHO in 1977 as "The marketing, distribution, prescription, and use of drugs in a society, with special emphasis on the resulting medical, social and economic implications". The main aim of conducting drug utilisation research is to facilitate rational use of drugs i,e the prescription of a well documented drug together with correct information at an affordable cost. Psychiatric disorders form an important public health priority among which psychotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…These results are approximately similar to the study conducted by R., B., et. al., where the average number of antipsychotics per prescription was 1.38 31 In our study,90.63% of antipsychotic drugs were prescribed by their generic names, which is less than the WHO recommendation of 100%. It is well recognized that substituting generic medicines for brand-name pharmaceuticals lowers the overall cost of therapy which is important in developing nations like India where most of our patients have poor socioeconomic profiles and is so advised.…”
Section: Analysis Of Who Core Indicatorscontrasting
confidence: 57%
See 2 more Smart Citations
“…These results are approximately similar to the study conducted by R., B., et. al., where the average number of antipsychotics per prescription was 1.38 31 In our study,90.63% of antipsychotic drugs were prescribed by their generic names, which is less than the WHO recommendation of 100%. It is well recognized that substituting generic medicines for brand-name pharmaceuticals lowers the overall cost of therapy which is important in developing nations like India where most of our patients have poor socioeconomic profiles and is so advised.…”
Section: Analysis Of Who Core Indicatorscontrasting
confidence: 57%
“…30 and also by R., B et.al., that concluded that Schizophrenia and other types of psychosis contributed, a major part to psychiatric morbidity. 31…”
Section: The Pattern Of Psychiatric Diagnosismentioning
confidence: 99%
See 1 more Smart Citation